2023
DOI: 10.3390/jimaging9060118
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Precision and Repeatability of Radiofrequency Echographic Multi Spectrometry (REMS) on Lumbar Spine and Proximal Femur: An In Vivo Study

Carmelo Messina,
Salvatore Gitto,
Roberta Colombo
et al.

Abstract: To determine the short-term intra-operator precision and inter-operator repeatability of radiofrequency echographic multi-spectrometry (REMS) at the lumbar spine (LS) and proximal femur (FEM). All patients underwent an ultrasound scan of the LS and FEM. Both precision and repeatability, expressed as root-mean-square coefficient of variation (RMS-CV) and least significant change (LSC) were obtained using data from two consecutive REMS acquisitions by the same operator or two different operators, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Indeed, the comparison procedure identifies the spectral modifications introduced by the physical properties of the bone structure, as reflected in the backscattered ultrasound signals. This process leads to the estimation of BMD and subsequently allows for diagnostic classification as healthy, osteopenic, or osteoporotic [ 16 , 17 ]. The intra-operator precision of REMS was 0.47% at the spine and 0.32% at the proximal femur evaluation, whereas the inter-operator precision was 0.55% and 0.51% at the lumbar spine and proximal femur, respectively [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the comparison procedure identifies the spectral modifications introduced by the physical properties of the bone structure, as reflected in the backscattered ultrasound signals. This process leads to the estimation of BMD and subsequently allows for diagnostic classification as healthy, osteopenic, or osteoporotic [ 16 , 17 ]. The intra-operator precision of REMS was 0.47% at the spine and 0.32% at the proximal femur evaluation, whereas the inter-operator precision was 0.55% and 0.51% at the lumbar spine and proximal femur, respectively [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Through the comparison of spectral characteristics in the analyzed signals with established reference spectral models for both pathological and normal conditions, it becomes possible to ascertain bone density [ 15 , 16 ]. A recent study by Messina et al [ 17 ], using data from two consecutive REMS acquisitions by the same operator or two different operators, respectively, demonstrated that both precision (expressed as the root-mean-square coefficient of variation) and repeatability (expressed as the least significant change) of REMS were not inferior to those of DXA. Furthermore, REMS, since it does not use ionizing radiation, can be employed even in subsets of patients for which DXA is not recommended, such as pregnant women, breast-feeding women, and children.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown a good diagnostic agreement between the BMD values obtained using the REMS technique compared to the DXA method. Moreover, REMS assessment was characterized by good repeatability and adequate precision but it was also able to predict the risk of fragility fractures [15][16][17]. In addition, REMS technology seems to be able to overcome some limitations of DXA, such as the overestimation of BMD in the presence of artifacts, osteophytes and fractures, and also to provide bone qualitative information [18,19].…”
Section: Introductionmentioning
confidence: 99%